Participation in Public Expenditure Systems : Participation in Public Expenditure Systems - World Bank (Washington, DC, 2012)
The mainstream public economics literature makes the case that government intervention ought to be considered in two instances, i) when market failures occur because of externalities, public good properties, incomplete information, and lack of competition, or ii) when market activities worsen distribution of income. After establishing at least one of these, the government chooses among a range of instruments to redress the resultant allocative as well as productive inefficiency. The instruments include regulation, tax or subsidy redressal, and public-funded private provisioning. In developing countries where absolute poverty, often rural and agrobased, is the biggest development challenge, provision of basic services like primary education and health, infrastructure, income generating and employment activities warrants state involvement for reasons stated. Because public spending is financed by domestic and international taxpayers (in the form of development credit), efficacy of public spending is not only important from a development effectiveness lens, but also because of accountability to the financiers of public spending which includes the poor who pay indirect taxes.